Differences in Gut Microbial Composition and Characteristics Among Three Populations of the Bamboo Pitviper (Viridovipera stejnegeri) - Jiaqi Zhang; Songwen Tan; Bing Lyu; Min Yu; Yue Lan; Ruixiang Tang; Zhenxin Fan; Peng Guo; Lei Shi (Ecology and Evolution)
ABSTRACT The gut microbiota contributes to host health by facilitating nutrient uptake, digestion, energy metabolism, intestinal development, vitamin synthesis, and immunomodulation, and plays an important role in the growth and reproduction of the animal itself. Considering the paucity of research on the gut microbiota of wild snakes, this study focused on bamboo pitviper (Viridovipera stejnegeri) populations from Anhui, Guizhou, and Hunan, with multiple fecal samples collected from each population (six, five, and three, respectively). Total microbial DNA was extracted from the fecal samples using metagenomic next‐generation sequencing and differences in gut microbial composition, abundance, and carbohydrate‐active enzymes (CAZymes) were analyzed and compared among the three populations. Results showed no significant variance in the α‐diversity of the gut microbes across the three populations, while principal coordinate analysis revealed significant differences in gut microbe composition. The four most abundant phyla in the gut microbiota of V. stejnegeri were Pseudomonadota, Bacteroidota, Actinomycetota, and Bacillota, while the four most abundant genera were Salmonella, Citrobacter, Bacteroides, and Yokenella. Linear discriminant analysis effect size demonstrated notable differences in gut microbial abundance among the three populations. Marked differences in CAZyme abundance were also observed across the microbial communities. Future studies should incorporate diverse ecological factors to evaluate their influence on the composition and function of gut microbiota.